RESISTANCE OF GOAT MEAT STORED ON ROOM TEMPERATURE - Gani, Vinensia Ghona; Swacita, Ida Bagus Ngurah; Agustina, Kadek Karang (Buletin Veteriner Udayana, 2022)
The purpose of this study was to determine the resistance of goat meat stored at room temperature. This study used a completely randomized design with 3 times of observation time, namely at the 8th, 16th and 24th hours in which 5 samples were examined for each observation. Testing of goat meat samples begins with subjective and objective physical tests, then the Eber test, then carried out a H2S test. The results showed that the five samples were not significantly different (P>0.05) with respect to consistency, texture, and significantly (P<0.05) in the color, smell, pH value, water content and water binding capacity, Eber test, and H2S test. At 16 and 24 hours, the color of the goats changes to brownish red, has a foul odor, the content becomes soft, the texture of the five meats has become coarse, a decrease in pH value, decreased water content and increased water binding capacity. In the Eber test, there was steam on the tube wall and for the H2S test, brown spots were seen on the tissue paper where this process of decay had occurred. From this research it can be concluded that, goat meat stored at room temperature decomposes at 16 hours. It is recommended that put the goat meat at room temperature, preferably no more than 16 hours and to maintain its quality, goat meat can be stored at cold temperatures.